Restriction Maps of Five Autographa californica MNPV Variants, Trichoplusia ni MNPV, and Galleria mellonella MNPV DNAs with Endonucleases SmaI, KpnI, BamHI, SacI, XhoI, and EcoRI - Smith, Gale E. (1979)
The restriction sites of Autographa californica nuclear polyhedrosis virus (AcMNPV) E2 DNA were mapped for the endonucleases SmaI, KpnI, BamHI, SacI, XhoI, and EcoRI. The restriction maps of four other AcMNPV variants, Trichoplusia ni (TnMNPV), and Galleria mellonella (GmMNPV) genomes were determined and compared to the endonuclease cleavage maps of AcMNPV E2 DNA. The viral structural polypeptides of AcMNPV variants S3, E2, S1, M3, and R9 were the same when analyzed by polyacrylamide gel electrophoresis. The major structural polypeptides of GmMNPV and TnMNPV had the same pattern in polyacrylamide gels as did AcMNPV structural polypeptides. GmMNPV and TnMNPV had several minor structural protein differences as compared with AcMNPV. AcMNPV variants, TnMNPV, and GmMNPV were distinct but with very similar genomes and protein structures.